Study of the Chinese Anostostomatidae (Orthoptera: Ensifera) IX: New additions of Anabropsis (Carnabropsis) from Yunnan Province - Bian, Xun (Zootaxa, 2024)
Based on the specimens deposited in Guangxi Normal University, Anabropsis (Carnabropsis) pusilla (Ingrisch, 2019) was recorded first in the fauna of China. Meanwhile, the female sex of A. (C.) karnyi (Wang, Liu & Li, 2015) was newly described.